Modeling of physiolsgical properties of stored human blood by complex impedance measurements - Sezdi, Manâ. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate of Biomedical Engineering, 2006., 2006)
In this study, the relationship between physiological properties of human blood,namely Na+, K+, Cl- concentrations, pH, 2,3-DPG and ATP, and its electrical parameters,the Cole-Cole parameters- the resistance of the extracellular fluid (Re), the resistance of the red cell interior fluid (Ri), phase angle (?), characteristic frequency (Fc) and thecapacitance of the cell membranes (Cm)- is investigated.Measurements are performed on 51 erythrocyte suspension (ES) samples, subject to42 days of storage at 4oC, on day 0, 10, 21, 35 and 42. On whole blood (WB) samples (31 samples) under 21 days of storage, same measurements are done on day 0, 10 and 21.Electrical measurements are performed in the frequency range from 100 kHz to 1 MHz atroom temperature. Multifrequency complex impedance data are fitted to Cole-Colediagrams using Least Mean Square algorithm to give Cole-Cole parameters for the equivalent electrical circuit model of blood samples.Variance analysis (ANOVA test) is used to evaluate differences in blood propertiesrelative to storage time. The relationship between the physiological and the electricalparameters of blood is investigated by regression analysis using SPSS. A multiple regression model is developed for ES and WB separately, where the physiologicalparameters are expressed in terms of the electrical parameters.In a case study, the models are tested for 20 donors, and it is seen that the model forWB is appropriate for predicting Na+, K+, Cl-, pH and ATP at all time, for ES the model is only appropriate for the first 35 storage days. The models can not estimate 2,3-DPG at all,at any time.This study clearly showed that complex impedance measurement technique can bea valuable tool in predicting the viability of stored blood.|Keywords: Na+-K+ ion current, Red blood cell, Blood storage lesions, Bioimpedance.
Keywords: Erythrocytes.; Blood banks.; Blood -- Collection and preservation.; Impedance, Bioelectric.